STUDY OF STRATEGIES FOR ESTABLISHING A NATIONAL WEALTH FUND FOR SUSTAINABLE PENSION - Nilubon Sivaborvornvatana,; Ornsasipachr Siriwonporn, (PEOPLE: International Journal of Social Sciences, 2025)
Thailand faces significant challenges in addressing the financial security and well-being of its aging population. With the demographic transition to a super-aged society imminent, this paper explores the potential of establishing a Sovereign Wealth Fund (SWF) to provide sustainable pensions for senior citizens. This study integrates demographic analysis, financial strategies, and theoretical frameworks such as Life-Course Theory to propose a model and strategy for a national pension fund. The findings underscore the importance of economic stability, comprehensive healthcare policies, and an age-friendly environment to address the multifaceted needs of the elderly population.